2001
DOI: 10.1002/1521-3757(20010216)113:4<758::aid-ange7580>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Shape Selectivity in Hydrocarbon Conversion

Abstract: Molecular sieves with three-dimensional framework structures find many applications in catalysis. [1, 2] A comprehensive and fundamental understanding of the product selectivity associated with these catalytic processes remains a formidable challenge of considerable practical significance. [3] Herein we focus on conversion reactions of alkanes. We demonstrate that molecular sieves favor the formation of reaction intermediates that have a shape commensurate with their pore shape. Bis(bidentate) catecholamide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…22 The critical role of entropy as channel occupation by adsorbed molecules increases has been specifically related to the ability of the zeolite structure to maximize effective length differences between linear and branched isomers. 15 A more general description, however, must include the specific role of protons and cations in determining adsorbate configurations and the frequency and reactive success by which molecules encounter others within zeolite pores (Scheme 3). The importance of analogous orientation effects on the coordination chemistry of saturated molecules is now being recognized 58 and led Bercaw and Labinger 59 to state that "the nature of the σ-complex will play a major, probably the major role in determining reactivity and especially selectivity in C-H bond activation processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The critical role of entropy as channel occupation by adsorbed molecules increases has been specifically related to the ability of the zeolite structure to maximize effective length differences between linear and branched isomers. 15 A more general description, however, must include the specific role of protons and cations in determining adsorbate configurations and the frequency and reactive success by which molecules encounter others within zeolite pores (Scheme 3). The importance of analogous orientation effects on the coordination chemistry of saturated molecules is now being recognized 58 and led Bercaw and Labinger 59 to state that "the nature of the σ-complex will play a major, probably the major role in determining reactivity and especially selectivity in C-H bond activation processes.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] The advent of medium-pore zeolites, with ten-membered ring structural channels of 0.5-0.6 nm dimensions led to experimental evidence and theoretical interpretations of shape selectivity, through which topological effects on reactivity reflect in general geometric factors and more specifically the exclusion of molecules or transition states based on size. [6][7][8][9][10][11] The strong effects of pore size and shape as they become "commensurate" with those of reacting species and the concomitant effects on enthalpies and entropies for adsorption and reaction have been noted broadly and convincingly; [12][13][14][15][16][17][18] these effects become less noticeable when reactants, products, and activated complexes are significantly smaller than the spaces within which reactions occur. For highsilica zeolites (with sites of uniform acid strength [19][20][21] ), with channels that allow facile entry and egress of reactants and products and within which transition states are not rigorously excluded by size, the local environment influences rates and reaction paths via subtle cooperative interactions that stabilize specific transition states.…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that framework topology is the predominating parameter determining for the positional branching selectivity of the zeolite. Some authors attributed the special branching patterns to differences in diffusivity of the respective isomers [10,[12][13][14]. According to such model of product diffusion, acid site concentration, microporosity and particle size all should alter the product distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Similar approaches and CBMC calculations led other authors to propose that the selectivity among the dimethylbranched isomers is also dominated by the relative diffusivities [10]. Schenk et al [14] calculated the free energy of formation of various dimethylbranched alkane isomers in TON type channels. Isomers with a spacing of the methyl groups matching with that of the lobes along the pore were estimated to diffuse slower than isomers the branching of which fitted less well with the arrangement of the lobes.…”
Section: Introductionmentioning
confidence: 94%
“…Remarkably, ED‐MIL‐101 reveals the size dependence on catalytic activities owing to the change of the substituent groups of carbonyl compounds in the Knoevenagel condensation. For example, with benzophenone, the condensation reaction with malonitrile is hard to realize (see the http://www.wiley-vch.de/contents/jc_2002/2008/z705998_s.pdf, Figure S6) because the formation of the quite large product, 1,1‐dicyano‐2,2‐diphenylethene, might be occluded in the pores, indicating the transition state or product shape‐selectivity already known in microporous zeolites 18. The size‐selective reactivity in ED‐MIL‐101 points out that the reaction essentially takes place in the amine‐grafted pores taking into consideration the guest‐selective properties of a 3D‐porous coordination polymer with amide groups in the base‐catalyzed Knoevenagel condensation 13b.…”
Section: Catalytic Properties Of the Amine‐grafted Mil‐101 And Mesopomentioning
confidence: 99%